2018
DOI: 10.1093/jme/tjy001
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-Mediated Knockdown of vATPase Subunits Affects Survival and Reproduction of Bed Bugs (Hemiptera: Cimicidae)

Abstract: The common bed bug, Cimex lectularius L. (Hemiptera: Cimicidae) has resurged as one of the most troublesome household pests affecting people across the globe. Bed bug infestations have increased in recent years primarily due to the evolution of insecticide resistance and the insect's ability to hitchhike with travelers. vATPases are one of the most evolutionarily conserved holoenzymes in eukaryotes, which are mainly involved in proton transport across the plasma membranes and intracellular organelles. RNA inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 43 publications
(37 reference statements)
2
25
0
Order By: Relevance
“…Mortality was below 20% in the dsactin injected females until 20 d but increased sharply above 80% thereafter. These results are consistent with previous results on RNAi induced mortality in bed bugs with vATPase-A , brahma, and vitellogenin (Moriyama et al 2016; Basnet and Kamble 2017, 2018). In other insects, such as Frankliniella occidentalis Pergande (Badillo-Vargas et al 2015), significant mortality was observed as early as 6 d post injection.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Mortality was below 20% in the dsactin injected females until 20 d but increased sharply above 80% thereafter. These results are consistent with previous results on RNAi induced mortality in bed bugs with vATPase-A , brahma, and vitellogenin (Moriyama et al 2016; Basnet and Kamble 2017, 2018). In other insects, such as Frankliniella occidentalis Pergande (Badillo-Vargas et al 2015), significant mortality was observed as early as 6 d post injection.…”
Section: Discussionsupporting
confidence: 93%
“…Rangasamy and Siegfried (2012) observed 100% mortality in 14 d after the knockdown of vATPase in D. v. virgifera . Gene knockdown and other phenotypes, such as reduced fecundity and survival, were observed within 1 wk, but it took a longer time to show the lethality in bed bugs (Basnet and Kamble 2017, 2018). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of pest control, gaining an understanding of the genes involved in gonadal differentiation and reproduction could make a considerable contribution toward the development of novel control strategies. Numerous genes have been investigated to evaluate their roles in the gonadal differentiation and reproduction of insects, including transformer 2 in the Asian citrus psyllid Diaphorina citri [22]; vATPase A , vATPase E , vitellogenin , and Brahma in the common bed bug Cimex lectularius [23,24,25]; lipase maturation factor in the grain aphid Sitobion avenae [26]; vitellogenin receptor and boule in D. virgifera virgifera [27]; Ran in the brown planthopper, Nilaparvata lugens [28]; Fatty acyl-Co A reductase in the cotton plant bug Adelphocoris suturalis [29]; and boule , Zero growth Population , double sex male , fzo, and gas8 in the fruit fly Bactrocera dorsalis [30]. Silencing these genes that are highly expressed in the ovary or testis has been shown to result in markedly reduced egg production and a lower rate of hatching.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that E. heros may carry active RNA-degrading enzymes in the hemolymph, we demonstrated that the delivery of dsRNA by microinjection successfully caused significant mortality when targeting mRNA from the vATPase (Fishilevich, Vélez, Storer, et al 2016b, Basnet and Kamble 2018a, Sato et al 2019, laccase Hattori 2016, Zhang et al 2018) and brahma genes(Basnet and Kamble 2018b), even when low levels of interference were obtained, as observed in many different insects. We also had expectations that the interference with the abundance of aquaporin-mRNA would cause a great distress in water balancing in E. heros, and induce high mortality as reported to other species (Raza et al 2016.…”
Section: Discussionmentioning
confidence: 68%